An open source platform addressing structural stability risk assessment in historical centres - Renzo Carlucci; Charilaos Maniatakis; Philip Fayad; Andrea Di Iorio; Nikolaos Schetakis; Costantine Spyrakos; Haris Saroglou; Alessio Di Iorio; Alexandros Paraskeuas; Nikos Papadopoulos (Groma, 2024)
The management of stability risk assessment in historical centres in a project that aims to design and develop an open platform where blocks of buildings and large structures may be represented in damage maps before the event occurs, addressing damage forecasts for seismic movements impacting on the structural stability of the CH. The structural stability is calculated using a Matlab code developed at the National Technical University of Athens, translated to an open source programming language (Python) using the software tool GeoPandas to enable operations that would normally require spatial database software (PostGIS). Furthermore, the use of open source technologies like QGIS desktop software will provide open and free access to view and contribute in the future.